Analisis Gerakan Literasi Sekolah di SD Islam Darul Huda Kecamatan Genuk Kota Semarang - Indar Khofifah; Arfilia Wijayanti; Fine Reffiane (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The purpose of this study was to describe the implementation of the School Literacy Movement and supporting infrastructure for the School Literacy Movement in SD Islam Darul Huda. This study uses a qualitative method. Data collection procedures in this study used observation techniques, interviews, questionnaires and documentation. The results showed that the School Literacy Movement at Darul Huda Islamic Elementary School, Genuk District, Semarang City was going well. The percentage with the highest result is 92% in class II, which means that the implementation of the School Literacy Movement has gone very well. The highest percentage of questionnaire results is in supporting facilities and infrastructure, namely class I with a result of 89%. Grades I to grade VI have implemented the School Literacy Movement. Supporting facilities and infrastructure for the School Literacy Movement at Darul Huda Islamic Elementary School, namely a library that provides fiction and non-fiction reading books in clean and comfortable conditions for reading, in each class there is no specific reading corner but there are bookshelves to store books.